Predicted distribution and habitat loss for the Endangered black-faced black spider monkey Ateles chamek in the Amazon. Issue 5 (18th September 2020) - Rabelo, Rafael M.; Gonçalves, Jonas R.; Silva, Felipe E.; Rocha, Daniel G.; Canale, Gustavo R.; Bernardo, Christine S.S.; Boubli, Jean P.
Abstract: The rate of deforestation in the Amazon is increasing. Predictive models estimate that as a result of agricultural expansion 40% of these forests will be lost by 2050. As a consequence the habitat of forest-dwelling species such as the Endangered black-faced black spider monkey Ateles chamek is being lost, particularly along the arc of deforestation in the Brazilian Amazon. We used species distribution modelling to (1) define the distribution of this spider monkey, using environmental predictors, (2) calculate the area of this distribution covered by the protected area network, and (3) calculate the expected loss of the species' habitat under future scenarios of deforestation. We found that the species occupies only c. 28% of its extent of occurrence. Only 32% of the species' area of occupancy is legally protected, and the modelling suggests that 31–40% of the species' habitat will be lost by 2050. We highlight three unprotected regions with extensive forest cover that are predicted to become severely deforested by 2050 as priority regions for expanding the protected area network. We also propose landscape management and restoration in three human-modified regions. Our study provides an example of how species distribution modelling can be applied to assess threats to species and support decision makers in implementing conservation actions.